Experimental and Finite Element Modeling of Self Compacted Reinforced Concrete Beams Strengthened by Bottom Steel Plates - M. Ali, Zaydon; A. Farhan, Jamal (Iraqi Journal of Civil Engineering, 2016)
In this study, eight rectangular reinforced concrete beams strengthened by bottom steel plates firmly interconnected to them by headed-stud shear connectors are manufactured using self compacting concrete and tested up to failure under two point loads to demonstrate the effect of steel-plate thicknesses, lengths, and the shear-connector distributions on the behavior, ductility and strength of this type of beams. A trial mix conforming to the EFNARC Constraints had been successfully carried out to satisfy the three fresh tests of SCC, these tests are flowability, passing ability and segregation resistance. The results show that there is a substantial improvement in the flexural resistance, increasing the flexural stiffness and decreasing the ductility ratio due to thickening steel plate, On contrary, increasing the spacing between shear connectors to 50% had slight effect on the flexural resistance, but subsequent increase of their spacing to 100% had seriously lowered that resistance, The spacing between shear connectors has a primary effect on the average flexural stiffness and ductility ratio. In regard to the steel plate length, its shortening has reduced the flexural resistance significantly, decreased the average flexural stiffness and had increased the ductility ratio. The experimentally determined ultimate flexural strength had been compared with its corresponding one computed by the "Strength Method" using ACI requirements where high agreement gained between them due to the nearly perfect interaction provided by SCC. The eight composite beams had also been analyzed by the non-linear three dimensional Finite Element Analysis employing ANSYS program (release 12.1),where high agreement is achieved compared with experimental results.